ANALISIS PENGARUH NPL, CAR, LDR, DAN ROA TERHADAP PENYALURAN KREDIT PADA PT BANK PEMBANGUNAN DAERAH JAWA TIMUR TBK - Putri, Elvika Nungki Chintia; Winarko, Sigit Puji; Widiawati, Hestin Sri (Jurnal Riset Akuntansi & Keuangan, 2024)
This research was conducted to analyze the influence of non-performing loans, capital adequacy ratio, loan to deposit ratio, and return on assets on credit distribution at PT Bank Pembangunan Daerah Jawa Timur Tbk. The subject studied was PT Bank Pembangunan Daerah Jawa Timur Tbk and the objects used were financial ratios in the form of Non-Performing Loans, Capital Adequacy Ratio, Loan to Deposite Ratio, and Return on Assets where 32 data were obtained. This type of research is causality research with a quantitative approach. Data analysis techniques use classical assumption tests, multiple linear regression analysis, coefficient of determination tests, and hypothesis tests. The program used is IBM Statistical Product and Service Solution (SPSS) Version 23. The results of this research show that partially the NPL and LDR variables have a significant effect on Credit Distribution, while the CAR and ROA variables do not have a significant effect on Credit Distribution. Simultaneously, the NPL, CAR, LDR and ROA variables together have a significant effect on the Credit Distribution variable